PENGARUH PENERIMAAN PAJAK BUMI DAN BANGUNAN TERHADAP PENDAPATAN ASLI DAERAH KOTA BANDUNG - Asep Dais Muharom; Fathi Rufaidah (Jurnal Financia : Akuntansi dan Keuangan, 2022)
Regional Original Income is the revenue obtained by the region itself. Regional revenue with the largest contribution comes from the taxation sector because this regional revenue is supported by the ability of the region to manage the output or source of each regional revenue that is used in developing and prospering the region itself. There are many factors that influence the size of the regional revenue itself. This study aims to determine how much influence the land and building tax revenue and advertisement tax partially and simultaneously on local revenue. The research method used is quantitative methods. The data from this study uses secondary data in the form of reports on the realization of local tax revenues from Badan Pengelola Daerah Kota Bandung and as well as data on the realization of Regional Budget from the Badang Pengelolaan Keuangan dan Aset Daerah Kota Bandung from 2013 to 2018. The results of this study It shows that land and building tax revenue has a significant effect on local revenue, advertisement tax revenue has no significant effect on local revenue and land and building tax revenue and billboards simultaneously have a significant effect on local revenue in Bandung City.